2022
DOI: 10.3390/d14090740
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Types Reveal Floral Diversity in Natural Honeys from Campeche, Mexico

Abstract: The Yucatan Peninsula, located in southern Mexico, is a central honey-producing region with extraordinary biodiversity of melliferous plants. Approximately 900 plant species have been described as being a source of nectar and pollen for bees and other pollinators. They provide ecosystem services that help to keep plant biodiversity high and mitigate the effects of climate change. This study aimed to reveal the diversity of the pollen content in honey through a melissopalynological analysis of 22 honey samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…According to the Shannon-Weiner diversity index, the samples with dominant pollen were less diverse, as described by Villalpando-Aguilar et al (2022). These authors reported lower (higher) pollen diversity in monofloral (multifloral) honeys.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to the Shannon-Weiner diversity index, the samples with dominant pollen were less diverse, as described by Villalpando-Aguilar et al (2022). These authors reported lower (higher) pollen diversity in monofloral (multifloral) honeys.…”
Section: Discussionmentioning
confidence: 95%
“…This could also be the case for Gymnopodium floribundum ‘ dzidzil che ’, a small tree species present in several vegetation types in Mesoamerica, including the states of Tabasco, Chiapas, and the Yucatan peninsula in Mexico (vicario-Mejía and Echazarreta 1999). It is known by beekeepers as one of the main floral resources for honey production in the Yucatan península (Villanueva-Gutiérrez et al 2009; Villalpando-Aguilar et al 2022). However, this species is also reported as a highly nectariferous plant, though low polliniferous (Porter-Bolland 2003; Coh-Martínez et al 2019), which could explain the low percentages in our pollen counts.…”
Section: Discussionmentioning
confidence: 99%
“…Honey may emanate both from single (unifloral honey) or multiple (multifloral honey) plant species depending on the diet of bees ( 25 ). In order to define the pollen inside the honey sample and therefore its type, melissopalynological analysis has been proven to be a reliable method ( 26 ).…”
Section: Introductionmentioning
confidence: 99%